Os impactos jurídicos da propagação de fake news na pandemia da COVID-19 - Oliveira, Luana Baenninger de (2024)
This final thesis aims to analyze the legal impacts of the spread of fake news related to COVID 19 in Brazil. Through a literature review and case law analysis, the study provides a brief recap of the main milestones of the pandemic that served as context for the widespread dissemination of health-related false information. It further examines the issue of misinformation and its direct impact on the health crisis, causing uncertainties about prevention methods, medication, modes of contagion, and mass vaccination. Additionally, the role of the Ministry of Health in combating misinformation was studied, including from the perspective of Decision 1873/2021 of the Federal Court of Accounts. The rights directly affected by the spread of fake news on health topics were also analyzed, along with the criminal and legislative repercussions of misinformation. To complement this work, case law from the São Paulo State Court of Justice is reviewed to understand the practical application of the subject, as well as the balance between the rights to information and freedom of expression. Finally, a series of permanent measures to combat health-related fake news is proposed